1989
DOI: 10.1177/37.4.2926122
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of S-100b protein in degenerating and regenerating rat sciatic nerves.

Abstract: We studied the cellular and subcellular distribution of S-100b protein in normal, crushed, and transected rat sciatic nerves by an immunocytochemical procedure. In uninjured nerves, S-100b protein was restricted to the cytoplasm and membranes of Schwann cells, with no reaction product present in the nucleus or in axons. Similar images were seen from the first to the thirtieth day after the crush in activated Schwann cells during the degeneration period, i.e., up to the seventh post-lesion day, and in normal Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
5

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 20 publications
4
19
0
5
Order By: Relevance
“…A similarly diffuse distribution of annexin V has been detected in Schwann cells in peripheral nerves. These localizations of annexin V strongly remind the subcellular localization of S-100 protein, a Ca2'-binding protein of the EF-hand type (for review see Donato, 1991), in the same cell types (Cocchia, 1981;Spreca et al, 1989). However, the amount of annexin Vlg of rat brain turned out to be -20% of that of S-100 protein in the same tissue (Donato, 1986).…”
Section: Discussionmentioning
confidence: 83%
“…A similarly diffuse distribution of annexin V has been detected in Schwann cells in peripheral nerves. These localizations of annexin V strongly remind the subcellular localization of S-100 protein, a Ca2'-binding protein of the EF-hand type (for review see Donato, 1991), in the same cell types (Cocchia, 1981;Spreca et al, 1989). However, the amount of annexin Vlg of rat brain turned out to be -20% of that of S-100 protein in the same tissue (Donato, 1986).…”
Section: Discussionmentioning
confidence: 83%
“…The expression of S100 protein in Schwann cells and sensory corpuscles is regulated by Schwann-related cell-axonic contact (DeLeon et al, 1991;Del Valle et al, 1993;Perez and Moore, 1968;Spreca et al 1989). In humans we demonstrated that nerve entrapment and section severely modifies the expression of S100 proteins by Meissner corpuscles.…”
Section: Peripheral Nervesmentioning
confidence: 78%
“…They are believed to participate in the regulation of energy metabolism, the regulation of cell shape and polarity, and intracellular calcium-regulated signal transduction [164]. The 10 kDa calcium-and zinc-binding [165][166][167] S100 protein is present in the cytoplasm and associated with plasma membranes of myelinating Schwann cells [168]. It is absent from compact myelin membranes [168,169], but is present at the Schmidt-Lanterman incisures and in the paranodal loops [169].…”
Section: E) S100mentioning
confidence: 99%